Juridical Review of Wiretapping Based on Law Number 1 of 2024 Amending Law Number 11 of 2008 on Electronic Information and Transactions Related to Criminal Acts at Bali Regional Police - Dedy Parta Kusuma; Erikson Sihotang; Komang Edy Dharma Saputra (Al-Makki Publisher, 2025)
Wiretapping, the act of intercepting conversations, is often viewed as a violation of human rights, particularly within law enforcement contexts. This research investigates the stages involved in implementing wiretapping as a means to uncover criminal offenses, while also identifying the challenges faced by the Bali Police in this process. Employing a normative research method complemented by empirical analysis, the study gathers data from various primary and secondary legal sources. This research aims to determine the stages of wiretapping implementation in uncovering criminal offenses and identify the obstacles faced by Bali Police in the process. The study reveals that while legal frameworks governing wiretapping exist, their practical application remains hindered by these obstacles. The mastery of advanced technology is essential for effective wiretapping, yet many investigators lack adequate training and resources. Additionally, external constraints, such as outdated equipment or insufficient legal support, further complicate the implementation process. In conclusion, this research highlights the dual nature of wiretapping as both a valuable tool for law enforcement and a potential infringement on individual privacy rights. Addressing the identified challenges is crucial for enhancing the effectiveness of law enforcement while ensuring the protection of citizens' rights. By improving technological proficiency and overcoming external limitations, Bali Police can better utilize wiretapping in their efforts to combat crime while respecting the principles of privacy and human rights.